2018
DOI: 10.1016/j.atmosenv.2018.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution of current-use pesticides in ambient air of Provence-Alpes-Côte-d’Azur Region and Corsica, France

Abstract: A total of 59 current-use pesticides were monitored in ambient air samples collected from February 2012 to December 2017, at two rural and six urban sites in Provence-Alpes-Côted'Azur Region and Corsica, France. 45 of searched active substances were detected at least in one sample, at frequencies ranging from 0.1 to 98.6%. Among the most frequently detected pesticides, we found the herbicide Pendimethalin (64.6%), the fungicide Tebuconazole (65.9%), and the insecticides Chlorpyrifos (71.5%) and Lindane (98.6%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Pesticides are of great interest for both the scientific community and the general public due to their worldwide uses and potential adverse health or environmental impacts (Carvalho, 2017;Inserm, 2013). They are present in the atmosphere in concentration levels from some picogram per cubic meter (pg m −3 ) to several nanograms per cubic meter (ng m −3 ) (Coscollà et al, 2013(Coscollà et al, , 2014Désert et al, 2018;Estellano et al, 2015;Lester et al, 2017;Zivan et al, 2016Zivan et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesticides are of great interest for both the scientific community and the general public due to their worldwide uses and potential adverse health or environmental impacts (Carvalho, 2017;Inserm, 2013). They are present in the atmosphere in concentration levels from some picogram per cubic meter (pg m −3 ) to several nanograms per cubic meter (ng m −3 ) (Coscollà et al, 2013(Coscollà et al, , 2014Désert et al, 2018;Estellano et al, 2015;Lester et al, 2017;Zivan et al, 2016Zivan et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were done with eight pesticides representative of various chemical classes of pesticides: cyprodinil (pyrimidine), deltamethrin (pyrethroid), difenoconazole (triazole), fipronil (pyrazole), oxadiazon (diazole), pendimethalin (dinitroaniline), permethrin (pyrethroid), and tetraconazole (triazole). The compounds under study were selected based on their distribution between gas and particle phases, their toxicity, and their presence in the atmosphere (Désert et al, 2018). Understanding the influence of these factors on the heterogeneous degradation kinetics of pesticides by OH radicals will help to better understand the atmospheric behavior and the atmospheric transportability of pesticides when they are adsorbed on atmospheric aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported the presence of pesticides in the atmosphere in concentrations ranging from a few picograms per cubic meter to hundreds of nanograms per cubic meter (Coscollà et al 2010;Estellano et al 2015;Lopez et al 2017;Désert et al 2018;Villiot et al 2018). At the same time, many adverse effects of pesticides on human health (Clementi et al 2008;Hatcher et al 2008;Marks et al 2010;Inserm 2013;Parrón et al 2014;Kim et al 2017) and on the environment (Santadino et al 2014;Carvalho 2017) have been evidenced.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study is to investigate the influence of the surface coating level (0.3 to 15% of a monolayer) on the heterogeneous ozonolysis of four pesticides (cyprodinil, deltamethrin, permethrin, and pendimethalin) adsorbed on two types of model mineral particles (hydrophobic and hydrophilic silicas). These four pesticides were selected based on their presence in the atmosphere up to a dozen of ng m -3 (Désert et al, 2018), on their toxicity M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 (APVMA, 2017), and on their distribution between the gas and particle phases (AOPWIN TM , Meylan and Howard 1993). Moreover, they have been the subject of numerous studies of reactivity towards ozone (Socorro et al 2015;Mattei et al 2018) and OH radicals (Socorro et al 2016;Mattei et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study is to investigate the heterogeneous reactivity with NO 3 radicals of eight current-use pesticides (cyprodinil (pyrimidine), deltamethrin (pyrethroid), difenoconazole (triazole), fipronil (pyrazole), oxadiazon (diazole), pendimethalin (dinitroaniline), permethrin (pyrethroid), and tetraconazole (triazole)) adsorbed on hydrophobic silica as a model for mineral atmospheric particles. The compounds under study were selected based on their distribution between gas and particle phases, their toxicity, their presence in the atmosphere (Désert et al, 2018). More, their heterogeneous reactivity was extensively investigated toward OH radicals (Socorro et al, 2016;Mattei et al, 2019a) and ozone (Socorro et al, 2015;Mattei et al, 2018Mattei et al, , 2019b.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%